The Intellectual Structure and Emerging Research Frontiers of Mathematical Reasoning in Cognitive Processes: A Bibliometric Analysis and Systematic Literature Review - Miratus Sholikha; Arif Abdul Haqq; Nasir Umar (Indonesian Journal of Teaching and Learning (INTEL), 2026)
Purpose – Mathematical reasoning has become a central focus of mathematics education research; however, existing evidence remains fragmented across cognitive, pedagogical, affective, and representational perspectives. Previous reviews have rarely integrated bibliometric mapping with systematic evidence synthesis to explain the intellectual development of this field. This study aims to examine the intellectual structure, thematic evolution, and emerging research frontiers of mathematical reasoning in cognitive processes. Methodology – This study employed a mixed-review design integrating bibliometric analysis and a Systematic Literature Review (SLR). Bibliographic data were retrieved from the Scopus database and selected using the PRISMA 2020 framework, resulting in 334 eligible journal articles. Bibliometric mapping was conducted using VOSviewer to analyse publication trends, country productivity, author collaboration, keyword co-occurrence, and density visualization, while qualitative synthesis was used to interpret thematic development and identify research gaps. Findings – The results reveal three major findings. First, scientific production has increased markedly since 2018, reflecting growing international interest in mathematical reasoning within cognitive processes. Second, mathematical reasoning functions as the intellectual hub linking cognitive, pedagogical, linguistic, semiotic, and affective perspectives. Third, affective constructs, particularly motivation and self-efficacy, remain underrepresented, highlighting important opportunities for future interdisciplinary research. Novelty – This study provides the first integrated synthesis combining bibliometric analysis and PRISMA-guided SLR to map the intellectual structure, thematic evolution, and research frontiers of mathematical reasoning in cognitive processes. Significance – The findings offer an evidence-based foundation for researchers, curriculum developers, and mathematics educators to develop more comprehensive theoretical models and interdisciplinary research agendas that integrate cognitive, affective, and instructional dimensions of mathematical reasoning.